Stochastic Energy-Transport Dispatch for Port Microgrid with Flexible Berth Allocation and Quay Crane Assignment - Xing, Ailing; Lu, Ying; Fang, Sidun; Niu, Tao; Chen, Guanhong; Liao, Ruijin (Conference record of the Industry Applications Conference, 2025)
To target the "carbon neutrality" goal and enhance energy efficiency, extensive electrification of ports become an inevitable trend, which tightly couples the adhered transport and energy sub-systems and forms port microgrids. In this paper, a stochastic energy-transport dispatch method is proposed based on the flexible berth allocation and quay crane assignment (BACA) for port microgrids, aiming to minimize the operation costs considering physical constraints such as the sequences of quay cranes and the draught depth of ships. Additionally, the proposed model explicitly accounts for the uncertainty inherent in ship arrival times, with an analysis conducted to evaluate the corresponding impact on operational costs. Comparative case studies demonstrate the proposed scheme can enhance the flexibility of the port microgrid, and show potentials to accommodate renewable energy.